EXPERIENCE OF INTRODUCING CLOUD TECHNOLOGIES - Kovalchuk, Vasyl; Shevchenko, lyudmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Modern education is closely connected with widespread digital technologies, through which communication, collaboration, creativity, and innovation can be organized. The aim and objectives of the article consist in describing the experience of real experience with cloud technologies on the example of a municipal organization (institution, establishment) “Shostka educational complex: specialized school of I-II degrees-lyceum of Shostka town council of Sumy region”. To test the effectiveness application of cloud computing technologies in the educational process of the institution, experimental work was carried out, as a result of which carried out: analysis of the possibility application of cloud computing technologies in the learning process; determination of pedagogical conditions application of cloud computing technologies in the learning process; testing the effectiveness of certain pedagogical conditions.Assessment of the possibility of using the selected technologies in education was carried out according to the results of a survey of all participants in the study. This stage made it possible to determine the main directions of research, take into account the possible obstacles to their use.To implement the selected pedagogical conditions, guidelines for teachers on the use of these technologies in the learning process were developed, which contain a set of methods and techniques for organizing lessons, ways to implement a business game, cluster, senkan, fishbone, comparison chart, brainstorming .Organizing the educational process with the help of cloud technology is one of the priority areas of updating modern education that allows not only to improve the quality of education, but also to achieve a new level of relations between participants in the educational process at all stages of teaching. They help teachers work not only with children but also with their parents.During the transition to the new educational standards, cloud technologies contribute to forming a new digital culture of teachers and students. Their applying in the educational allows to make the educational space open.